2015
DOI: 10.1016/j.sleh.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Sleep maintenance difficulties in insomnia are associated with increased incidence of hypertension

Abstract: This study provides novel information regarding the risk of hypertension in insomnia via sleep maintenance difficulties. Findings from this study provide preliminary evidence for examining nighttime fluctuations of blood pressure and concomitant physiological changes (ie, catecholamines, heart rate, and sympathetic activation) due to wake during sleep as a mechanism for subsequent hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In our study, regularly reporting waking up during the night (i.e., 16–30 times a month), feeling unrested during the day, feeling overly sleepy during the day, and trouble falling asleep were moderately associated with the MHO phenotype [ 43 ]. However, some chronic conditions, for example, diabetes, hypertension, obesity (the clinical diagnosis), and depression, are also associated with fragmented sleep, insomnia, and excessive daytime sleepiness [ 44 , 45 ]. Therefore, further research in this area is needed to better understand the relationship between various sleep quality factors and cardiometabolic health amongst those living with obesity/higher bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, regularly reporting waking up during the night (i.e., 16–30 times a month), feeling unrested during the day, feeling overly sleepy during the day, and trouble falling asleep were moderately associated with the MHO phenotype [ 43 ]. However, some chronic conditions, for example, diabetes, hypertension, obesity (the clinical diagnosis), and depression, are also associated with fragmented sleep, insomnia, and excessive daytime sleepiness [ 44 , 45 ]. Therefore, further research in this area is needed to better understand the relationship between various sleep quality factors and cardiometabolic health amongst those living with obesity/higher bodyweight.…”
Section: Discussionmentioning
confidence: 99%
“…The current study focuses on SMI defined as when individuals experience wakefulness during the night or early morning before their intended waking time and have difficulty falling back to sleep (Waters et al, 1993). The construct of SMI has been widely used in previous studies which suggest sleep maintenance difficulty increases the risk for mental disorders (Meeker et al, 2019), hypertension (Cheng et al, 2015), and greater healthcare utilization (Bolge et al, 2010). It remains unclear what aspects of their role and context contribute to SMI among dementia caregivers.…”
Section: Sleep Disturbance and Family Caregivers Of Pwdmentioning
confidence: 99%
“…However, the most likely effect of these measurement errors would be to draw the observed associations toward null. Despite these limitations, the prospective study design, objectively measured sleep parameters from an average of 15 days and blood pressure measured at baseline and follow‐up were major strengths compared with the previous prospective studies that used self‐reported sleep parameters (Cheng, Pillai, Mengel, Roth, & Drake, 2015; Lin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%